Bis(benzimidazole) dinuclear silver(I) complex modified carbon paste electrode for electrochemical sensing of hydrogen peroxide. Issue 15 (17th December 2021) - Sun, Fugang; Dong, Jianping; Jiang, Yuxuan; Li, Ruixue; Wu, Huilu
Abstract: A carbon paste electrode (CPE) modified with a new bis(benzimidazole) dinuclear Ag(I) complex was developed as an electrochemical sensor to quickly and accurately identify hydrogen peroxide. The dinuclear Ag(I) complex, [Ag2 (BBP)2 ( p -tso)2 ], was prepared by reaction of 1, 3-bis(1H-benzimidazole-2-yl)propane (BBP) with p -toluenesulfonate ( p -tso). The Ag(I) complex was studied by elemental analysis, IR and UV-Vis spectra, and single-crystal X-ray diffraction. The Ag(I) complex is a dinuclear metallacycle with twofold rotational symmetry in which two syn-conformational BBP are connected by two linearly coordinated Ag(I) ions. Each Ag(I) has three-coordinate T-shaped geometry. The electrochemical sensing performance of the Ag(I) complex modified carbon paste electrode (Ag-CPE) toward H2 O2 was evaluated by cyclic voltammogram and chronoamperometry in 0.2 M phosphate-buffered saline (PBS, pH = 6). Linear relationships between the peak currents and the scan rates showed that the electrochemical reaction on Ag-CPE is controlled by dynamics. Moreover, the electrochemical sensor for H2 O2 was found to have a linear response from 0.5 μM to 4.0 mM with a detection limit of 0.42 μM and also revealed good anti-interference ability and stability. These studies proved that the Ag-CPE can be used as an electrochemical H2 O2 sensor. Graphical Abstract: UF0001